The Isatin Scaffold: Exceptional Potential for the Design of Potent Bioactive Molecules - Nazir, Habiba; Naseer, Muhammad Moazzam (Synlett, 2025)
Since its discovery the isatin scaffold has been recognized for its significance, but it gained particular attention after being isolated from natural sources and identified as a natural product. This discovery prompted extensive research into its synthesis, as well as its chemical and biological applications. The isatin scaffold undergoes several key chemical reactions, including oxidation, reduction, ring expansion, Friedel–Crafts reactions, and aldol condensation, resulting in the formation of biologically active compounds such as 2-oxindoles, tryptanthrin, indirubins, and others. In recent years, numerous derivatives of isatin, particularly those involving substitution at nitrogen and the C3 and C5 positions, have been synthesized and investigated for their diverse biological activities, with some even receiving FDA approval as therapeutic agents. This account provides a concise overview of the isatin scaffold, highlighting its synthesis, reactivity, and structural features of the scaffold as well as those of its main derivatives, particularly their ability to engage in various non-covalent interactions. Additionally, the selected recent biological applications of isatin derivatives are discussed, with an emphasis on contributions from our own research group. The goal is to enhance the understanding of the potential of the isatin scaffold as a platform for designing potent bioactive molecules, with an optimistic outlook on its future in drug development.1 Introduction2 Synthesis of the Isatin Scaffold3 Tautomerism, Reactivity, and Functionalization Sites of the Isatin Scaffold4 Structural Features of the Isatin Scaffold and Its Derivatives5 Potent Bioactive Molecules from the Isatin Scaffold5.1 N-Functionalization5.2 C3-Functionalization5.3 N- and C3-Functionalization5.4 C5-, C5,N-, and C5,N,C3-Functionalization6 Coordination Chemistry of Isatin Scaffold Derived Compounds7 Conclusions and Outlook
Keywords: isatin; reactivity; non-covalent interactions; bioactivity